2012
DOI: 10.1108/10569211211204492
|View full text |Cite
|
Sign up to set email alerts
|

Trade openness and economic growth: further evidence without relying on data stationarity

Abstract: Purpose -The purpose of this paper is to investigate the relationship between trade openness and economic growth in developing countries. Under this aim, the co-integration relationship between trade openness and economic growth of 17 developing countries is examined without relying on data stationarity. Design/methodology/approach -The co-integration relationship between trade openness and economic growth is analyzed by Bounds testing approach developed by Pesaran et al. In addition to this, the causality rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Likewise with research (Ono & Uchida, 2018) which found that government spending on education increases human capital so that wage levels increase and ultimately will increase production output which has an impact on increasing economic growth. In accordance with the research conducted by (Liang, 2010) that human capital in health has a positive and significant effect on economic growth. In line with research by (Ogundari, Kolawole., 2017) that human capital has a positive influence on economic growth, and a greater influence is the influence of the health sector for economic growth.…”
Section: Effect Of Human Capital On Economic Growthsupporting
confidence: 89%
“…Likewise with research (Ono & Uchida, 2018) which found that government spending on education increases human capital so that wage levels increase and ultimately will increase production output which has an impact on increasing economic growth. In accordance with the research conducted by (Liang, 2010) that human capital in health has a positive and significant effect on economic growth. In line with research by (Ogundari, Kolawole., 2017) that human capital has a positive influence on economic growth, and a greater influence is the influence of the health sector for economic growth.…”
Section: Effect Of Human Capital On Economic Growthsupporting
confidence: 89%